The tripeptide feG regulates the production of intracellular reactive oxygen species by neutrophils - Davison Joseph S; Mathison Ronald D (BMC, 2006)
Abstract Background The D-isomeric form of the tripeptide FEG (feG) is a potent anti-inflammatory agent that suppresses type I hypersensitivity (IgE-mediated allergic) reactions in several animal species. One of feG's primary actions is to inhibit leukocyte activation resulting in loss of their adhesive and migratory properties. Since activation of neutrophils is often associated with an increase in respiratory burst with the generation of reactive oxygen species (ROS), we examined the effect of feG on the respiratory burst in neutrophils of antigen-sensitized rats. A role for protein kinase C (PKC) in the actions of feG was evaluated by using selective isoform inhibitors for PKC. Results At 18h after antigen (ovalbumin) challenge of sensitized Sprague-Dawley rats a pronounced neutrophilia occurred; a response that was reduced in animals treated with feG (100 μg/kg). With antigen-challenged animals the protein kinase C (PKC) activator, PMA, significantly increased intracellular ROS of circulating neutrophils, as determined by flow cytometry using the fluorescent probe dihydrorhodamine-123. This increase was prevented by treatment with feG at the time of antigen challenge. The inhibitor of PKCδ, rottlerin, which effectively prevented intracellular ROS production by circulating neutrophils of animals receiving a naïve antigen, failed to inhibit PMA-stimulated ROS production if the animals were challenged with antigen. feG treatment, however, re-established the inhibitory effects of the PKCδ inhibitor on intracellular ROS production. The extracellular release of superoxide anion, evaluated by measuring the oxidative reduction of cytochrome C, was neither modified by antigen challenge nor feG treatment. However, hispidin, an inhibitor of PKCβ, inhibited the release of superoxide anion from circulating leukocytes in all groups of animals. feG prevented the increased expression of the β1-integrin CD49d on the circulating neutrophils elicited by antigen challenge. Conclusion feG reduces the capacity of circulating neutrophils to generate intracellular ROS consequent to an allergic reaction by preventing the deregulation of PKCδ. This action of feG may be related to the reduction in antigen-induced up-regulation of CD49d expression on circulating neutrophils.